Gap detection responses modelled using the Hill equation in adults with well-controlled HIV. (2nd May 2023) - Niemczak, Christopher E.; Cox, Christopher; Grigoryan, Gevorg; Springer, Gayle; Fellows, Abigail M.; Torre, Peter; Hoffman, Howard J.; Buckey, Jay C.; Plankey, Michael W.
Abstract: Objective: This study's objective was determining whether gap detection deficits are present in a longstanding cohort of people living with HIV (PLWH) compared to those living without HIV (PLWOH) using a new gap detection modelling technique (i.e. fitting gap responses using the Hill equation and analysing the individual gap detection resulting curves with non-linear statistics). This approach provides a measure of both gap threshold and the steepness of the gap length/correct detection relationship. Design: The relationship between the correct identification rate at each gap length was modelled using the Hill equation. Results were analysed using a nonlinear mixed-effect regression model. Study sample: 45 PLWH (age range 41–78) and 39 PLWOH (age range 38–79) were enrolled and completed gap detection testing. Results: The likelihood ratio statistic comparing the full regression model with the HIV effects to the null model, assuming one population curve for both groups, was highly significant ( p < 0.001), suggesting a less precise relationship between gap length and correct detection in PLWH. Conclusions: PLWH showed degraded gap detection ability compared to PLWOH, likely due to central nervous system effects of HIV infection or treatment. The Hill equation provided a new approach for modelling gap detection ability.